Pola Asuh Demokrasi dan Nilai-Nilai Agama Dalam Keluarga di Lingkungan Beragam Agama Desa Suka Julu Dusun III Jumpa - Laili Alfita; Risydah Fadillah; Muhammad Irsan Barus (Pelita Masyarakat, 2019)
This service aims at this service is Building a pattern of Democratic Care and Building the values of Religion. It should be understood that the family is two or more individuals who live in one household because of the relationship of blood, marriage and interacting with one another, having their respective roles by creating and maintaining a culture. The environment that is first encountered by children is the family environment. In the family of course there are religious values born from generation to generation and carried by the family. Whereas religious experience is an element of feeling in religious consciousness, namely the feeling that leads to beliefs generated by actions or amaliyah. Suka Julu Village Hamlet III Jumpa is one of the villages located in Karo land with diverse religious communities although it is dominated by Karo tribes in the area around Berastagi city. In customs, girls are not allowed to talk with their father. In addition, there is still a lack of planting of religious values. There are still those who do not have strong religious beliefs, so that on Christmas day, there are still Muslims who follow Christian activities and vice versa. This is certainly confusing for children. So that it will give birth to children who lack confidence. Personality dynamics actively influence human activities. Spiritual energy functions to regulate spiritual activities such as thinking, remembering, observing and so on. The instinct function regulates primary needs: eating, drinking and sexual. The ego has the function of adjusting impulse adjustment with objective reality. While Super Ego functions as a giver of inner rewards (satisfied, happy, successful) and punishment (guilt, sin, regret). The reward is played by the ideal ego, and inner punishment is carried out by the conscience. This activity was carried out to foster democratic upbringing and religious values in families in various religious environments in a tribe.